Innate immunity response of zafirlukast treated-tilapia during foreign body inflammation - Oliveira, Susana Luporini de [UNESP]; Costa, Camila Carlino da [UNESP]; Aracati, Mayumi Fernanda [UNESP]; Rodrigues, Leticia Franchin [UNESP]; Conde, Gabriel [UNESP]; Moraes, Alessandra Cristina de; Camplesi, Annelise Carla [UNESP]; Farias, Thais Heloisa Vaz [UNESP]; Silva, Ives Charlie [UNESP]; Pereira, Luiz Arthur Malta; Belo, Marco Antonio de Andrade [UNESP] (Elsevier, 2024)
There is limited knowledge regarding the blockade of cysteinyl leukotriene receptors (CysLTRs) and their effects in teleost fish. The present study investigated the effects of Zafirlukast, antagonist of CysLTR1 receptor, on the foreign body inflammatory reaction in Nile tilapia (Oreochromis niloticus). Zafirlukast-treated tilapia demonstrated a decrease in the formation of multinucleated foreign body giant cells and Langhans cells on the round glass coverslips implanted in the subcutaneous tissue, along with a significant reduction in white blood cell counts and decreased production of reactive oxygen species. There was an increase in serum levels of α2-macroglobulins, as well as a decrease in ceruloplasmin and haptoglobin. Zafirlukast treatment led to a significant decrease in the area of splenic melanomacrophage centers and a reduction in the presence of lipofuscin. These findings highlight the potential anti-inflammatory effects of zafirlukast treatment in tilapia and indicate its action on CysLTR1 receptor, modulating the innate immune response of tilapia during the foreign body reaction. The comprehension of chronic inflammation mechanisms in fish has become increasingly relevant, especially concerning the utilization of biomaterials for vaccine and drug delivery.
Keywords: Acute phase proteins; Anti-inflammatory; Leukotrienes; Melanomacrophages; Oreochromis niloticus; Oxidative stress